Klasiber: A Floss Implementation to Build e-Learning System of Faculty of Industrial Technology, Islamic University of Indonesia; an Administrator Perspective - Mukhammad Andri Setiawan (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
Open Source (OS) community offers numerous e-learning platforms called: Learning Management Systems (LMS). These applications deliver what teacher and students need in the learning processes. The accessibility of e-learning provides additional challenges that may not be faced when providing access to other Web resources. This paper provides a set of guidelines and experiences for building an online course based on the e-learning standards using free/libre/open source software (FLOSS) applications with Moodle which has been implemented in Faculty of Industrial Technology and can be accessed through the website at http://klasiber.informatika.web.id. The experience of the LMS will facilitate in deepen the dissemination of the knowledge through online course materials, forum and discussion, assignment, and collaborative work.Keywords: LMS, Moodle, e-learning